IMPLEMENTASI MODEL PEMBELAJARAN KREATIF DAN PRODUKTIF DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN GURU - Purnama, Diana Septi (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Education effort is especial in improvement of human resource quality owning high creativity and high independence very strategic looked into productive and creative learning model in the effort developing Human Resource matching with growth of world of IPTEK, to gain professional in his area. Human resources which was quality started from the attending of certifiable grad. In realizing quality of grade from each every education institution, can be strived to [pass/through] activity of learning. Teacher have duty and role in choosing and developing strategy learning of which can give experience learn & developing student potency in an optimal fashion in order to become human being of inovative, adaptive and creative. Education process which is condusive where student can learn with pleasure and excite so that have autodidact motivation which is andal. Other assumption express that school have failed is not in presenting academic profile but in strengthening relation link which is the full of warm feeling, constructive, can grow to feel each other loving and can bear selfregard sense of belonging, this was necessary for teacher to reach efficacy of learning.